The judge's discretion in resolving disputes of judicial separation - ابراهيم, حارث علي; هلال, سليمان محمد (Journal of Legal Sciences, 2021)
Marriage is in fact a year of God's years in his creation, and it is the only method that God has made the right way to breed and reproduce and to continue life among people, and God did not make the almighty man like other creatures, he did not let his instincts go off without order and a correct way for her, he did not leave to chaos in Instinct is a place but guided and directed creation to the right way and way of life between people and reproduction in order to preserve the dignity of the human being and his exposure from chaos. However, marriage may experience some problems, difficulties, disagreement or discord between the spouses and even to the extent that it prevents the continuation of the common life between them, and one of the spouses is attacked on the right of the other, so it is necessary to return the aggressor to the right. Since divorce is in the hands of the man and not in the wife's hands and he uses it whenever he wishes, however, the Shariah has given the woman what she has to do with her right and dignity from transgressing her husband and harming her, so she has granted the wife the right to seek judicial separation and termination ofmarriage.